Community-Based Organisation in a Transition Society: The Case of Balinese Ormas Conflict - I Nyoman Sudama; Adrianus Eliasta Sembiring Meliala (Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
Transitions in Balinese society as a result of internal conflict are critical opportunities to discover solutions for a better future for the society. The problem is how to investigate the conflict as part of the Balinese transitional development stages. Thus, the objective of this research is to answer that problem by examining the irregular transition stages of mass organization, also known as ‘ormas’ in Bahasa Indonesia, as a Balinese Community-Based Organisation (CBO) to get a better insight into Balinese society's transformation. This research employs a mixed method covering quantitative and qualitative descriptive data analysis. The qualitative data is collected by employing explorative key informant interviews while a survey of 519 respondents in six regions including Tabanan, Gianyar, Badung, Karangasem, Buleleng, and Denpasar is the source of quantitative data. The analysis presents the early stage of Balinese ‘ormas’ development followed by major issues and contradictions of the ‘ormas’ based on Balinese community perceptions. The main finding is that there were distortions in ‘ormas’ life cycles that hid their comparative advantages to become an ideal CBO. This paper concludes that ‘ormas’ transformation is the important step toward ideal CBO as part of Balinese community development. Therefore, adopting Lewin’s change model with general practical steps as well as some policing practices can support the future development of Balinese CBOs for a better contribution to Balinese communities.